2023
DOI: 10.1039/d2ta09061a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced visible-light photocatalytic antibacterial activity of metal–organic framework/gold nanocomposites

Abstract: The use of metal-organic frameworks (MOFs) to achieve excellent photocatalytic antibacterial properties have attracted considerable attention. However, insufficient visible light absorption and rapid electron-hole recombination are two crucial issues for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In contrast, the absorption edge of AuKN showed a significant red-shift, and an absorption peak could be observed at 520 nm, attributing to the surface plasmon resonance (SPR) band of Au NPs. 46 The results indicated that the modification with Au NPs tuned the light absorption of KN from ultraviolet region to visible light, and it was consistent with the existent papers. Raja et al modified potassium niobate with palladium nanoparticles, and the SPR effect of palladium adjusted the light absorption of potassium niobate toward visible light.…”
Section: Characterization Of Aukn-lasupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the absorption edge of AuKN showed a significant red-shift, and an absorption peak could be observed at 520 nm, attributing to the surface plasmon resonance (SPR) band of Au NPs. 46 The results indicated that the modification with Au NPs tuned the light absorption of KN from ultraviolet region to visible light, and it was consistent with the existent papers. Raja et al modified potassium niobate with palladium nanoparticles, and the SPR effect of palladium adjusted the light absorption of potassium niobate toward visible light.…”
Section: Characterization Of Aukn-lasupporting
confidence: 89%
“…Pure KN exhibited an absorption band at the edge of 400 nm, indicating its strong absorption in the ultraviolet region. In contrast, the absorption edge of AuKN showed a significant red-shift, and an absorption peak could be observed at 520 nm, attributing to the surface plasmon resonance (SPR) band of Au NPs . The results indicated that the modification with Au NPs tuned the light absorption of KN from ultraviolet region to visible light, and it was consistent with the existent papers.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Researchers have studied and reported air filters and masks endowed with photo-responsive properties. [48][49][50][51] Li et al investigated the potential of metal-organic frameworks (MOFs) for air pollution control and personal protection, focusing on a zinc-imidazolate MOF with photocatalytic bactericidal properties. 48 The fabricated MOF-based air filters not only achieve efficient particulate matter removal but also demonstrate remarkable photocatalytic antibacterial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic NPs have demonstrated their versatility over the decades, owing to their adjustable size, structure, morphology, composition, and fascinating optical characteristics [6][7][8]. The literature contains well-documented production procedures for numerous types of metal nanoparticles [9][10][11][12][13][14][15]. Metallic nanostructures, particularly colloidal gold NPs, are used in biomedical applications due to their ease of production, simplicity, and speed of bioconjugation [16].…”
Section: Introductionmentioning
confidence: 99%